Prognostic Factors in Anti-glomerular Basement Membrane Disease: A Multicenter Study of 119 Patients - Marques, Cindy; Carvelli, Julien; Biard, Lucie; Faguer, Stanislas; Provôt, François; Matignon, Marie; Boffa, Jean-Jacques; Plaisier, Emmanuelle; Hertig, Alexandre; Touzot, Maxime; Moranne, Olivier; Belenfant, Xavier; et al. (Frontiers in Immunology, 2019)
We report the overall and renal outcome in a French nationwide multicenter cohort of 119 patients with anti-glomerular basement membrane (anti-GBM) disease. Sixty-four patients (54%) had an exclusive renal involvement, 7 (6%) an isolated alveolar hemorrhage and 48 (40%) a combined renal and pulmonary involvement. Initial renal replacement therapy (RRT) was required in 78% of patients; 82% received plasmapheresis, 82% cyclophosphamide and 9% rituximab. ANCA positive (28%) patients were older (70 vs. 47 years, p<0.0001), less frequently smokers (26 vs. 54%, p=0.03) and had less pulmonary involvement than ANCA- patients. The 5 years overall survival was 92%. Risk factors of death (n=11, 9.2%) were age at onset HR 4.10 per decade (1.89-8.88) p=0.003, hypertension HR 19.9 (2.52-157.2) p=0.005, dyslipidemia HR 11.1 (2.72-45) p=0.0008 and need for mechanical ventilation HR 5.20 (1.02-26.4) p=0.047. The use of plasmapheresis was associated with better survival HR 0.29 (0.08-0.98) p=0.046. At 3 months, 55 (46%) patients had end-stage renal disease (ESRD) versus 37 (31%) ESRD-free and 27 (23%) unevaluable with follow-up < 3 months. ESRD patients were older, more frequently female and had a higher serum creatinine level at presentation than those without ESRD. ESRD-free survival was evaluated in patients alive without ESRD at 3 months (n=37) using a landmark approach. In conclusion, this large French nationwide study identifies prognosis factors of renal and overall survival in anti-GBM patients.